Pulmonary lymphoid tissue induced after SARS-CoV-2 infection in rhesus macaques - Zhong-Min Ma; Katherine J. Olstad; Katherine J. Olstad; Koen K. A. Van Rompay; Koen K. A. Van Rompay; Smita S. Iyer; Smita S. Iyer; Smita S. Iyer; Christopher J. Miller; Christopher J. Miller; Christopher J. Miller; J. Rachel Reader; et al. (Frontiers in Immunology)
IntroductionLung diseases are widespread worldwide. Pulmonary immunity plays a vital role against lung pathogens, including SARS-CoV-2 infection. Understanding the pathogenesis, including the development of local immune responses to infection, is fundamental for developing interventions to control the viral infection.MethodsUsing immunohistochemistry, we investigated the distribution of immune cells in the lungs of rhesus macaques experimentally infected with SARS-CoV-2 and euthanized 11–14 days later.ResultsTertiary lymphoid tissue was found in all SARS-CoV-2 infected animals. The number (13.9 vs 1.5 iPLT number/ lung cm2), size (25992 vs 13946 µm2) and total area (0.46 vs 0.02 mm2 iPLT/ lung cm2) of the lymphoid tissue aggregations were significantly higher in SARS-CoV-2 infected animals than that of normal controls. This induced pulmonary lymphoid tissues comprised B cells, T cells, CD169 macrophages, and follicular dendritic cells with evidence of lymphocyte priming and differentiation.DiscussionThe results suggest local immunity plays an important role in the SARS-CoV-2 infection. Further study of pulmonary immunity could lead to new interventions to develop vaccine strategies and discover new immune-regulatory biomarkers in monitoring and controlling SARS-CoV-2 infection and other lung diseases.